KORELASI LATAR BELAKANG SOSIAL KELUARGA DENGAN PRESTASI AKADEMIK MAHASISWA FISIP UNIVERSITAS RIAU T.A 2015-2018 - Setia, Kelara; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study is (1) To determine the social background of the Sociology student family. (2) To find out the academic achievements of Sociology students. (3) To find out the correlation between social background and academic achievement of students of the Faculty of Social and Political Sciences, University of Riau. This study uses quantitative descriptive. By using sampling techniques used porporion method or Provotional Random Sampling. The subjects of this study were Sociology students of the Faculty of Social Sciences and Political Sciences of the University of Riau in 2015-2018 as many as 62 people. Data analysis using Pearson Product Moment Correlation (PPM) Specifications. The results showed that the independent variables had a significant positive effect on academic achievement with a correlation coefficient of 0.527 with a significance value of 0.000 less than 0.05. then it can be interpreted there is a positive and significant relationship between social background and academic achievement.  Keywords: Parents, Academic Achievement